Incidentally detected multilocular cystic renal cell carcinoma: a case report - Rajput, Manharsinh; Sarma, Priyanku; Deka, Phanindra Mohan (International Surgery Journal, 2021)
Multilocular cystic renal cell carcinoma (RCC) is a tumor of low-grade malignant potential which is curable by surgical resection. Here, we report a case which was incidentally detected during evaluation of right flank pain. It’s very challenging to differentiate such lesions from conventional clear cell carcinoma. However, it has good prognosis and amenable to surgical resection.